Creation and Adoption of Energy-related Innovations - the Main Facts - Spyridon Arvanitis; Michael Peneder; Christian Rammer; Andrin Spescha; Tobias Stucki; Martin Wörter (ETH Zurich, KOF Swiss Economic Institute, 2016)
One of the main goals of the "Energy Strategy 2050" in Switzerland is the exploitation of the existing energy efficiency potentials. The size of the efficiency potential strongly depends on the development and the adoption of energy-related innovations. The objective of this project is to improve our knowledge about the drivers and potentials of both the adoption and the creation of energy-saving technologies and other technologies for the generation of renewable energy sources through a comparative firm-level study for Switzerland, Germany and Austria. Firms are not only the main source of energy-related innovation, but they are also responsible for a considerable share of the total energy consumption. The data presented in this study has been collected through firm surveys conducted in all three countries at the same time. The surveys used a harmonized questionnaire and collected information both on the development and on the adoption of energy-related innovations during the years 2012 to 2014. While data on the adoption of energy-related technologies has been obtained for all major economic sectors (manufacturing, construction and services, excluding state-related services such as public administration, education and health and excluding the energy sector) data on the development of energy-related innovations has only been collected for a group of manufacturing sectors (excluding food, textiles and clothing, printing, pharmaceuticals, and "other manufacturing") as well as two service sectors, "information technology services" and "technical services".
Keywords: 330; Energieeinsparung; Energietechnik; Innovation; Erneuerbare Energie; Innovationsakzeptanz; Vergleich; Schweiz; Deutschland; Österreich